Multi-environment meta-analysis reveals the mechanism of action of potassium-solubilizing microorganisms on crop yields - Fan, Xing; Zhu, Yuanpeng; Jia, Yan; Du, Peishen; Wang, Weini; Liu, Junmei; Lv, Zhijun; Liu, Ronghao; Li, Xiaobin (Frontiers in Plant Science, 2025)
The availability of soil potassium plays a critical role in yield increases. Potassium-solubilizing microorganisms (KSM) offer a promising biological solution to improve potassium availability, but their efficacy across diverse global environments remains uncertain. Through a global meta-analysis of 102 studies (846 paired observations), we systematically evaluated the effects of KSM application on crop yields across five key dimensions: microorganism types, soil factors, crop classifications, field management, and stress types. KSM inoculation significantly increased soil available potassium (+28.9%), crop yield (+23.4%), and key growth indices, such as root length (+29.50%) and leaf area (+44.7%). This study identified Aspergillus spp. as the most suitable microorganism, and revealed that KSM efficacy is highly dependent on context: yield responses were greatest in clay loam soils, vegetable crops, and greenhouse conditions. Structural equation modeling indicated that microbial abundance, climate, soil available potassium, and plant growth (root length and leaf area) are key direct and indirect drivers of yield enhancement. The results indicate that the application of KSM is an effective strategy to increase crop yields in various environments. By identifying the optimal conditions for KSM application, the identification of optimal application parameters, derived from cross-study analysis, provides a robust strategy for leveraging microbial communities to boost soil potassium availability and nutrient efficiency, thereby contributing to the transition toward more sustainable and climate-resilient agriculture.